Do recessions accelerate routine-biased technological change? Evidence from vacancy postings - Brad J. Hershbein; Lisa B. Kahn (W.E. Upjohn Institute for Employment Research, 2016)
Routine-biased technological change (RBTC), whereby routine-task jobs are replaced by machines and overseas labor, shifts demand towards high- and low-skill jobs, resulting in job polarization of the U.S. labor market. We test whether recessions accelerate this process. In doing so we establish a new fact about the demand for skill over the business cycle. Using a new database containing the near-universe of electronic job vacancies that span the Great Recession, we find evidence of upskilling - firms demanding more-skilled workers when local employment growth is slower. We find that upskilling is sizable in magnitude and largely due to changes in skill requirements within firm-occupation cells. We argue that upskilling is driven primarily by firm restructuring of production towards more-skilled workers. We show that 1) skill demand remains elevated after local economies recover from the Great Recession, driven primarily by the same firms that upskilled early in the recovery; 2) among publicly traded firms in our data, those that upskill more also increase capital stock by more over the same time period; and 3) upskilling is concentrated within routine-task occupations - those most vulnerable to RBTC. Our result is unlikely to be driven by firms opportunistically seeking to hire more-skilled workers in a slack labor market, and we rule out other cyclical explanations. We thus present the first direct evidence that the Great Recession precipitated new technological adoption.
Keywords: D22; E32; J23; J24; M51; O33; 330; Job polarization; job postings; RBTC; recessions; routine-biased technological change; upskilling; vacancies; Konjunktur; Wirtschaftskrise; Rationalisierung; Technischer Fortschritt; Anforderungsprofil; Hochqualifizierte Arbeitskräfte; Regionaler Arbeitsmarkt; Offene Stellen; Schätzung; USA